WEBVTT
00:00:00.600 --> 00:00:06.520
Simplify six to the power of negative three multiplied by three all over two to the power of negative one.
00:00:07.440 --> 00:00:13.240
To begin, itโs sensible to begin by evaluating each of the numbers in this expression which have exponents.
00:00:13.800 --> 00:00:18.000
They are six to the power of negative three and two to the power of negative one.
00:00:18.520 --> 00:00:22.320
But what does a negative power or a negative exponent actually mean?
00:00:23.280 --> 00:00:27.200
Well, a negative exponent tells us to find the reciprocal of that number.
00:00:27.840 --> 00:00:32.760
So ๐ to the power of negative ๐ is equal to one over ๐ to the power of ๐.
00:00:33.440 --> 00:00:39.600
For example, two to the power of negative three is equal to one over two to the power of three.
00:00:40.160 --> 00:00:49.200
And since two to the power of three is eight, we can say that two to the power of negative three is the same as one-eighth.
00:00:49.720 --> 00:00:52.560
And it works in much a similar way when weโre dealing with fractions.
00:00:52.920 --> 00:00:58.680
Four-thirds to the power of negative two is the same as three-quarters squared.
00:00:59.080 --> 00:01:03.680
And this is because the reciprocal of four-thirds is three-quarters.
00:01:04.360 --> 00:01:06.680
We can then evaluate the numerator.
00:01:07.120 --> 00:01:08.920
Three squared is nine.
00:01:09.240 --> 00:01:13.160
And the denominator, four squared is 16.
00:01:13.640 --> 00:01:19.680
So four-thirds all squared is the same as nine 16ths.
00:01:20.120 --> 00:01:23.880
Letโs use this to evaluate six to the power of negative three.
00:01:24.440 --> 00:01:26.760
The reciprocal of six is one-sixth.
00:01:27.160 --> 00:01:31.880
So six to the power of negative three is one over six cubed.
00:01:32.560 --> 00:01:34.560
We could evaluate six cubed.
00:01:35.040 --> 00:01:37.760
But itโs probably not the most sensible step to take.
00:01:38.280 --> 00:01:40.520
And weโll see why in a moment.
00:01:41.000 --> 00:01:43.160
The reciprocal of two is one-half.
00:01:43.720 --> 00:01:48.880
So two to the power of negative one is one over two to the power of one.
00:01:49.400 --> 00:01:57.000
And since anything to the power of one is just itself, itโs the same as one-half.
00:01:57.400 --> 00:01:59.720
So letโs rewrite our expression piece by piece.
00:02:00.360 --> 00:02:04.920
Itโs one over six cubed multiplied by three all over one-half.
00:02:05.480 --> 00:02:09.200
And next, we recall the fact that this fraction line means divide.
00:02:09.840 --> 00:02:13.280
And to divide by a fraction, we multiply by the reciprocal of that fraction.
00:02:13.840 --> 00:02:19.400
So this is the same as one over six cubed multiplied by three multiplied by two over one.
00:02:20.000 --> 00:02:22.920
Now multiplication is commutative.
00:02:23.160 --> 00:02:25.600
It can be done in any order.
00:02:26.120 --> 00:02:28.400
So we donโt really need these brackets here.
00:02:28.920 --> 00:02:32.000
And we add a denominator of one to the number three.
00:02:32.520 --> 00:02:33.880
We then multiply the numerators.
00:02:34.400 --> 00:02:37.120
One multiplied by three multiplied by two is six.
00:02:37.560 --> 00:02:42.720
And six cubed multiplied by one multiplied by one gives us a denominator of six cubed.
00:02:43.480 --> 00:02:47.960
Now remember, six is the same as six to the power of one.
00:02:48.480 --> 00:02:52.320
And this time, we recall this rule.
00:02:52.560 --> 00:02:56.920
๐ฅ to the power of ๐ divided by ๐ฅ to the power of ๐ is ๐ฅ to the power of ๐ minus ๐.
00:02:57.640 --> 00:03:04.080
When we divide as long as the basis that sees big numbers are the same, we can subtract the exponents.
00:03:04.480 --> 00:03:07.880
So, one minus three is negative two.
00:03:08.520 --> 00:03:16.120
And we can see that six to the power of one divided by six to the power of three is six to the power of negative two.
00:03:16.520 --> 00:03:21.080
And weโve already seen that a negative power tells us to find the reciprocal.
00:03:21.600 --> 00:03:26.400
So six to the power of negative two is one over six squared.
00:03:26.960 --> 00:03:36.160
And since six squared is 36, we can say that one over six squared is the same as one 36th.
00:03:36.560 --> 00:03:41.320
And we have fully simplified this expression.
00:03:41.960 --> 00:03:50.720
Six to the power of negative three multiplied by three over two to the power of negative one is the same as one 36th.